Removal of disperse red 9 from textile wastewater using acid activated carbon and polypyrrole nano composite – A comparative study - Supriya, S.; Palanisamy, P.N. (IJRDO-Journal of Applied Science, 2016)
The present study analyses the feasibility of removing Disperse red 9 (DR9) from industrial effluents using two different adsorbents namely Phosphoric acid impregnated Activated Carbon (PAC) and Polypyrrole Polymer Composite (PPC) prepared from Casuarina wood. Batch mode adsorption studies were performed in order to investigate the adsorption capacities of these adsorbents by varying initial dye concentration, agitation time, temperature and pH. A comparative study on the adsorptive capacities of PAC and PPC were carried out and it was inferred that PPC had better adsorption capacity than PAC at an initial concentration of 50 mg/L at 300C, 350C & 400C. The calculated qe values agree very well with experimental values. The regression coefficient values above 0.98 confirm that adsorption follows second order kinetics. The increase in Langmuir adsorption capacity (Q0) from 7.48 to 9.41 mg/g for PAC and 8.65 to 11.73 mg/g for PPC on increasing the temperature from 300 to 400C accounts for the endothermic nature of the process.